Greenhouse gas emissions and nutrient management in East African livestock systems - Leitner, Sonja (International Livestock Research Institute, 2025)
Lecture on GHG emissions and nutrient cycling in mixed crop-livestock and pastoral systems in East Africa, held at the University of Hohenheim as part of the Lecture series on "Livestock Systems and Development